A rare cytogenetically cryptic MECOM rearrangement in a patient with myelodysplastic neoplasm and SF3B1 mutation identified by RNA sequencing: a case report - Jin, Ye; Xu, Zi-Jun; Lv, Chao-Ran; Qian, Zhen; Wen, Xiang-Mei; Xiao, Sheng; Lin, Jiang; Qian, Jun (Frontiers in Oncology, 2026)
MECOM (the MDS1 and EVI1 complex locus) rearrangements have been identified as an independent high-risk factor in acute myeloid leukemia (AML). The diversity of MECOM rearrangement partner genes significantly influences disease mechanisms and prognosis. The majority of atypical MECOM rearrangements result in EVI1 overexpression through translocation into super-enhancer-containing regions. This report describes a rare, recurrent MBNL1::MECOM rearrangement identified in a myelodysplastic neoplasm (MDS) patient with a concurrent SF3B1 mutation. Although conventional cytogenetics showed a normal karyotype, the rearrangement was confirmed by next-generation sequencing (NGS) and fluorescence in situ hybridization (FISH). Concurrently, the patient exhibited high EVI1 expression, consistent with the common mechanism observed in atypical MECOM rearrangements. Given the well-documented association between SF3B1 mutations and MECOM rearrangements, analysis of MECOM expression and RNA sequencing (RNA-seq) is crucial for SF3B1-mutated patients, even in the absence of elevated blast counts. Furthermore, this case underscores the need for further research into the synergistic biological role of spliceosome mutations and MECOM rearrangements in driving leukemia.